Characterization of Lignocellulolytic Bacteria from Gut of Termite (Isoptera: Rhinotermitidae and Termitidae) - Putri Dwi Mulyani; Muhammad Rizky Ulil Albab; Yekti Asih Purwestri (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2021)
A total of 10 bacterial isolates have been isolated from the gut of termites (Isoptera: Rhinotermitidae and Termitidae) and are known to have the ability to produce lignocellulolytic enzymes consisting of cellulase, laccase, and lignin peroxidase. The enzymatic ability allows these bacteria to be used as a source of new enzymes in the industrial world. However, further research on the character of bacteria to support identification has not been carried out. This study aims to characterize lignocellulolytic bacteria in the gut of termites morphologically and biochemically. Morphological observations were carried out including colony shape, colony edge, colony color, growth type, bacterial cell shape, and gram staining. Meanwhile, the biochemical characterization carried out included glucose fermentation test, indole formation, starch hydrolysis, catalase test, and nitrate reduction. The results showed that ten isolates of lignocellulolytic bacteria from the gut of termites (Isoptera: Rhinotermitidae and Termitidae) grew facultatively anaerobic, had almost similar morphological characters, with colony shapes including irregular and filamentous, colony edges in the form of lobate, undulate, and filamentous, and coloration. Colonies are white to yellowish white. The result of gram staining showed that most of the bacteria were gram positive bacteria with coccus and bacillus shaped bacterial cells. Biochemical analysis showed that these bacteria have the ability to ferment glucose, hydrolyze starch, reduce hydrogen peroxide (HÃ¢ââOÃ¢ââ 30%) and reduce nitrate.ÃÂ